2014
DOI: 10.1186/1477-3155-12-12
|View full text |Cite
|
Sign up to set email alerts
|

A new ex vivo method to evaluate the performance of candidate MRI contrast agents: a proof-of-concept study

Abstract: BackgroundMagnetic resonance imaging (MRI) plays an important role in tumor detection/diagnosis. The use of exogenous contrast agents (CAs) helps to improve the discrimination between lesion and neighbouring tissue, but most of the currently available CAs are non-specific. Assessing the performance of new, selective CAs requires exhaustive assays and large amounts of material. Accordingly, in a preliminary screening of new CAs, it is important to choose candidate compounds with good potential for in vivo effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…These authors also observed high mobility of carbon nanoparticles inside plant and seed tissues. In general, CBNMs have been found to be highly mobile in plant tissues, depending on the applied nanoparticle [8,59]. Further biochemical, genomic and proteomic studies are needed to fully understand FNPs mobility and physiological activities in plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors also observed high mobility of carbon nanoparticles inside plant and seed tissues. In general, CBNMs have been found to be highly mobile in plant tissues, depending on the applied nanoparticle [8,59]. Further biochemical, genomic and proteomic studies are needed to fully understand FNPs mobility and physiological activities in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, carbon based nanomaterials (CBNMs) have been the focus of several studies in recent years, and have been shown to be helpful in both agriculture and biotechnology [7,8]. The most investigated CBNMs are fullerene (C 60 and C 70 ), fullerenol C 60 (OH) x , x = 18–36 and CNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical chemical reactions may be used, giving rise to water soluble compounds such as forming terpenoid salts [ 41 ]. Another strategy relies on the development of stable nanosystems, which can improve water solubility of these substances by entrapping then into micelles with nano-size diameter [ 42 ]. Nanobiotechnology is an emerging area with great potential for innovative products, including eco-friendly pesticides.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a factor of ca. 3-fold decrease in 1 has been described for nanoparticulated Gd quelates between 1.4 and 7 [20]. Still, additional contributions could come from the fact that compounds described in [18] were glyconjugates, providing second-sphere water molecules close to the chelated Gd, with increased bulk relaxivity.…”
Section: Resultsmentioning
confidence: 99%